Клад с джучидскими монетами из местности “Равна гора” у села Оброчище вблизи Балчика - Лазаров, Л. (Степи Европы в эпоху средневековья, 2008)
The paper deals with a hoard of 16 dirhems of the end of the 13th c. from “Ravna Gora” territory located between Obrochische village and Albena resort of Balchik region, Dobrich province.